(untitled) (Pragyaratna प्रज्ञारत्न, 2023)
Teaching practice is a training course for the students of Faculty of Education at Tribhuvan University, Nepal. To make teaching practice realistic, practical, skillful, and meaningful, a collaborative approach and information communication technology (ICT) tools play a significant role in mathematics classrooms. In this context, this research study explores the context of student teachers’ teaching practice to use engagement learning approaches integrated with ICT tools in the mathematics classroom. Bruner’s theory of learning and Kearsley and Shneiderman’s engagement theory have been used as theoretical referents of this study. The methodology section comprises class observation of student teachers and an interview session with the head teacher, class teacher, student teacher, and each boy and girl student. The results reveal that an engagement learning strategy enhances interest and confidence among student groups, which is linked to knowledge, strengthening and skill growth for producing qualified human resources in mathematics. This research motivates students, mathematics teachers, and teacher educators.